Acute Toxicity and Dermal and Eye Irritation of the Aqueous and Hydroalcoholic Extracts of the Seeds of "Zapote" Pouteria mammosa (L.) Cronquist. (26th July 2015) - Dutok, Carlos M. S.; Berenguer-Rivas, Clara Azalea; Rodríguez-Leblanch, Elizabeth; Pérez-Jackson, Liliana; Chil-Nuñez, Idelsy; Escalona-Arranz, Julio César; Reyes-Tur, Bernardo; Queiroz, Margareth M. C.
Abstract : The common use of Pouteria mammosa (L.) Cronquist, "Mamey or Zapote, " in food and ethnobotanic medicine shows its low or absent toxicity as fruit extracts prepared from seeds. However, it is essential to conduct security trials to scientifically support their use in drug therapy. This study evaluated the aqueous and hydroalcoholic extract (25%) Acute Oral Toxicity, obtained from the seeds of P. mammosa, in Sprague Dawley rats and dermal and eye irritability in New Zealand rabbits. The 404 and 405 acute dermal and eye irritation/corrosion guidelines were used, as well as the 423 Acute Oral Toxicity guideline, Acute Toxic Class Method of the Organization for Economic Cooperation and Development (OECD). The aqueous extract was located in the following category: not classified as toxic (CTA 5), while hydroalcoholic extract at 25% was classified as dangerous (CTA 4). Both extracts can be used without side reaction that irritates the skin which permitted classification as potentially not irritant. P. mammosa in the two extracts caused mild and reversible eye irritation, and it was classified as slightly irritating.